Tracking long-term landscape change : habitat connectivity for moose and fisher in Tŝilhqot’in territory ... - Grohovsky, Matthew (University of British Columbia, 2021)
Traditional ecological knowledge and values of Indigenous peoples are increasingly incorporated into resource management. However, science still lacks sufficient examples of collaborative research with Indigenous communities. To explore the potential of geospatial approaches in this regard, I examined changes in habitat connectivity from 1984 to 2019 for two species of significance to the Tŝilhqot’in First Nation: fisher (Pekania pennanti) and moose (Alces alces). Within the Tŝilhqot’in traditional territory, I used existing geospatial datasets in conjunction with ecological literature to map fisher and moose habitat suitability over time. Then, these suitability ratings were used as proxies for animal movement to create resistance surfaces. These resistance surfaces were further used in a long-term connectivity analysis for each species (via Linkage Mapper software) throughout the study area and within a highly disturbed sub-region. Connectivity was quantified using measures of patch size, corridors (i.e. ...